Measuring skill and chance in different versions of Poker - Lambrecht, Marco (Discussion paper series, 2020)
This paper aims to measure skill and chance in different versions of online poker, using the best-fit Elo algorithm established in the first chapter. While Texas Hold'em arguably is the most popular version being played, the amount of skill involved might differ from other versions like Omaha Hold'em. Many platforms offer faster procedures to play (e.g. "hyper turbo"), as well as different levels of stakes. Given the richness of online poker data, it is possible to isolate the impact of these variations individually. The heterogeneity of best-fit Elo ratings decreases in quicker competitions or with higher stakes. Meanwhile, Omaha seems to contain more elements of skill than Texas Hold'em, as its analysis shows a wider distribution of skill levels of players.
Keywords: Graue Literatur